2017
DOI: 10.1002/path.4938
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma‐associated single‐nucleotide variants and deletions identified by the use of genome‐wide high‐throughput analysis of hepatitis B virus

Abstract: This study investigated hepatitis B virus (HBV) single-nucleotide variants (SNVs) and deletion mutations linked with hepatocellular carcinoma (HCC). Ninety-three HCC patients and 108 non-HCC patients were enrolled for HBV genome-wide next-generation sequencing (NGS) analysis. A systematic literature review and a meta-analysis were performed to validate NGS-defined HCC-associated SNVs and deletions. The experimental results identified 60 NGS-defined HCC-associated SNVs, including 41 novel SNVs, and their pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 158 publications
(172 reference statements)
0
40
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12] As viral factors from nucleotide sequencing analyses, core promoter mutations, precore mutations, core mutations, and Pre-S deletions have been reported. 10,13,14 Recently, the hepatitis B X protein genotype was reported to be associated with HCC development and HCC proliferation in vitro and in vivo. 15 Additionally, some single-nucleotide polymorphisms in several genes including HLA class I and II have been shown to be associated with HBV-related HCC.…”
Section: H Epatitis B Virus (Hbv) Infection Is a Worldwidementioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12] As viral factors from nucleotide sequencing analyses, core promoter mutations, precore mutations, core mutations, and Pre-S deletions have been reported. 10,13,14 Recently, the hepatitis B X protein genotype was reported to be associated with HCC development and HCC proliferation in vitro and in vivo. 15 Additionally, some single-nucleotide polymorphisms in several genes including HLA class I and II have been shown to be associated with HBV-related HCC.…”
Section: H Epatitis B Virus (Hbv) Infection Is a Worldwidementioning
confidence: 99%
“…Several cohorts have identified the risk factors for HBV‐related HCC, such as age, male sex, albumin, platelet counts (PLT), advanced fibrosis/liver cirrhosis, HBV DNA, and hepatitis B core‐related antigen (HBcrAg) . As viral factors from nucleotide sequencing analyses, core promoter mutations, precore mutations, core mutations, and Pre‐S deletions have been reported . Recently, the hepatitis B X protein genotype was reported to be associated with HCC development and HCC proliferation in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the integration mechanisms of the viral genome, specific mutations in the X regions, pre-core, core-promoter and pre-S may increase the risk of developing HCC [39,40] . Among the most frequent mutations at the nuclear promoter level, the double mutation A1762T/G1764A is closely related to the probability of developing HCC.…”
Section: Pathogenic Mechanisms Of Hbv-related Hccmentioning
confidence: 99%
“…The predictive value of HBV preS deletion on the occurrence of HCC in patients chronically infected with HBV has been confirmed in a prospective study [54] . Recent deep sequencing analysis has demonstrated that the preS deletions involving a specific fragment (nt2977-3013) in HBV genotype C are significantly associated with HCC [55] . These epidemiological evidences indicate that the HBV mutations including preS deletion, A1762T/G1764A, C1653T, and T1753V are the etiological factors of HBVinduced HCC.…”
Section: Reduction Of Cd8mentioning
confidence: 99%
“…Mutations in the preS and S regions also notably facilitate carcinogenesis. Transfection of Huh7 cells with the large S region with preS deletion has shown that HCC-associated single-nucleotide variants (SNVs) in the small surface region of HBV genome influence carcinogenesis pathways, including endoplasmic reticulum-stress and DNA repair systems [55] . The HBV large envelope protein gene fragment (preS1/ preS2/S), with F141L mutation in the preS2 region, can significantly promote the proliferation of hepatocytes by downregulating the p53 and p21 pathways and upregulating the expression of cyclin-dependent kinase 4 and cyclin A.…”
Section: Reduction Of Cd8mentioning
confidence: 99%